Body composition and cardiorespiratory fitness in overweight or obese people post COVID-19: A comparative study - Lemos, Maurício Medeiros; Cavalini, Gustavo Rocha; Pugliese Henrique, Carlos Renato; Perli, Victor Augusto Santos; de Moraes Marchiori, Glória; Marchiori, Luciana Lozza de Moraes; Sordi, Ana Flávia; Franzói de Moraes, Solange Marta; de Paula Ramos, Solange; Valdés-Badilla, Pablo; Mota, Jorge; Magnani Branco, Braulio Henrique (Frontiers in Physiology, 2022)
The present study aimed to evaluate the body composition and cardiorespiratory fitness of overweight or obese people after COVID-19. 171 volunteers of both sexes (men, n=93 and women, n=78) between 19 and 65 years old were allocated into three groups according to the severity of their symptoms of COVID-19: non-hospitalized people/mild symptoms (n=61), hospitalized (n=58), and hospitalized in an intensive care unit-ICU (n=52). Two laboratory visits were carried out 24 hours apart. First, a medical consultation was carried out, with subsequent measurement of body weight and height (calculation of body mass index) and body composition assessment via electrical bioimpedance. After 24 hours, a cardiorespiratory test was performed using the Bruce protocol, with a direct gas exchange analysis. Hospitalized individuals had significantly higher values for fat mass and body fat percentage than non-hospitalized individuals (p<0.05). Significantly higher values were found for heart rate (HR) and peak oxygen consumption (VO2peak) for individuals who were not hospitalized when compared to those hospitalized in the ICU (p<0.05). Significantly higher values for distance, ventilation, and the relationship between respiratory quotient were found for non-hospitalized individuals compared to hospitalized individuals and those in the ICU (p<0.05). After the cardiorespiratory test, higher values for peripheral oxygen saturation (SpO2) were observed for non-hospitalized individuals than for all hospitalized individuals (p<0.05). Diastolic blood pressure was significantly higher at the fifth- and tenth-minute post-Bruce test in hospitalized than in non-hospitalized participants (p<0.05). Based on these results, proposals for cardiopulmonary rehabilitation are indispensable for hospitalized groups considering the responses of blood pressure. Monitoring HR, SpO2, and blood pressure are necessary during rehabilitation to avoid possible physical complications. Volume and intensity of exercise prescription should respect the physiologic adaptation. Given lower physical conditioning among all the groups, proposals for recovering from health conditions are urgent and indispensable for COVID-19 survivors. Keywords: exercise test; obesity; outcome and process assessment, health care; delivery of health care; physical fitness.